Vaccine Hesitancy Amidst COVID-19 Pandemic: Insights from a Focus Group Study in Croatia - Pavić, Željko; Dremel, Anita; Pintarić, Ljiljana; Kovačević, Emma; Lesinger, Gordana (Italian Sociological Review, 2022)
Even though vaccination has been regarded as historically one of the most successful public health interventions, vaccine hesitancy still remains an important health issue. In order to explore this issue, the authors conducted four asynchronous online focus groups with the total of 40 Croatian citizens. Drawing on iterative thematic analysis, three emerging overarching reasons of vaccine hesitancy were determined: risk perception (cost-benefit ratio), belief in natural immunity and institutional distrust. In addition, three possible cross-cutting topics emerged: communication with healthcare workers, influence of media, social media and the Internet, and COVID-19 pandemic. A widespread dissatisfaction with healthcare workers is tentatively explained by proposing the concept of ‘false autonomy’ of patients when making vaccination decisions. As for the COVID-19 context, the participants often cited their awareness of the profit-driven healthcare system in conjunction with the development of COVID-19 vaccines. The authors conclude by framing the study results into the wider social context of individualistic consumerism, postmodern health beliefs and the characteristics of Croatian healthcare system, as well by calling for more in-depth studies of vaccine hesitancy.